Civil wars beyond their borders: the human capital and health consequences of hosting refugees - Javier E. Baez (Institute for the Study of Labor (IZA), 2008)
Between 1993 and 1994, extremist militia groups carried out the extermination of ethnic Tutsis and moderate Hutus in the genocides of Burundi and Rwanda. Nearly one million people were killed and thousands were forcibly uprooted from their homes. Over the course of a few months, Kagera - a region in northwestern Tanzania - received more than 500,000 refugees from these wars. This region is home to a series of geographic natural barriers, which resulted in variation in refugee intensity. I exploit this variation to investigate the short and long run causal effects of hosting refugees on the outcomes of local children. Reduced-form estimates offer evidence of adverse impacts almost 1.5 years after the shock: a worsening of children's anthropometrics of 0.3 standard deviations, an increase of 15 to 20 percentage points in the incidence of infectious diseases and an increase of roughly 7 percentage points in mortality for children under five. I also exploit intra- and inter-cohort variation and find that childhood exposure to this massive arrival of refugees reduced height in early adulthood by 1.8 cm (1.2%), schooling by 0.2 years (7.1%) and literacy by 7 percentage points (8.6%). Designs using the distance from the village to the border with Rwanda as an alternative instrumental strategy for refugee intensity support the findings. The estimates are robust across a variety of samples, specifications and estimation methods and provide evidence of a previously undocumented indirect effect of civil wars on the well-being of children and subsequent economic growth in refugee-hosting communities.
urn:nbn:de:101:1-2008042524
Keywords: O10; 330; Civil conflicts; refugees; children; human capital; health; Africa; Flüchtlinge; Bürgerkrieg; Kinder; Gesundheit; Humankapital; Afrika; Tansania